Relationship among serum metabolic hormones with pregnancy rates to fixed-time artificial insemination in Bos indicus beef females - Peres, R. F.G. [UNESP]; Cooke, R. F.; Dias, H. [UNESP]; Keisler, D. H.; Pohler, K. G.; Vasconcelos, J. L.M. [UNESP] (Elsevier, 2021)
Two experiments compared body parameters and serum concentrations of GH, IGF-I, and leptin in Bos indicus females based on their pregnancy status to fixed-time artificial insemination (FTAI). In Exp. 1, 226 nulliparous heifers were assigned to a puberty induction protocol (d -35 to d -23), followed by an estrus synchronization and FTAI protocol (d -11 to 0). Heifers received a controlled internal progesterone releasing insert (CIDR) previously used three times on d -35, followed by 0.6 mg of estradiol cypionate and CIDR removal on d -23. Heifers received 2 mg of estradiol benzoate and a CIDR previously used twice on d -11, 12.5 mg of dinoprost tromethamine in addition to CIDR removal, 0.6 mg of estradiol cypionate and a 200 IU of eCG on d -2, followed by FTAI on d 0. Heifer BW and BCS were recorded on d -35, -11, and 30, whereas blood samples were collected on d -35, -23, -11, 0, and 30. In Exp. 2, 821 multiparous lactating Nelore beef cows were assigned to the estrus synchronization and FTAI protocol described in Exp. 1, but received 300 IU of eCG on d -2. Cow BW and BCS were recorded on d -11 and 30, and blood samples were collected on d -11, 0, and 30. In both experiments, pregnancy status was verified via transrectal ultrasonography on d 30. In Exp. 1, heifers that became pregnant had greater (P = 0.03) IGF-I concentrations on d 0 and less (P = 0.05) IGF-I concentrations on d 30 compared to heifers that did not become pregnant (pregnancy status × day; P < 0.01). No differences in BW, BCS, GH and leptin were detected (P ≥ 0.23) according to heifer pregnancy status. In Exp. 2, cows that became pregnant had less (P = 0.03) leptin concentrations on d -11, and less (P = 0.01) IGF-I concentrations on d 30 compared to cows that did not become pregnant (pregnancy status × day; P ≤ 0.05). No differences in BW, BCS, and GH were detected (P ≥ 0.15) according to cow pregnancy status. In summary, serum leptin at the beginning of estrus synchronization was negatively associated with pregnancy rates to FTAI in multiparous cows. A negative relationship was also observed between serum IGF-I during early gestation with pregnancy rates to FTAI across parities. These results provide novel insights on the relationships among metabolic hormones with reproductive performance of B. indicus females.
Keywords: Beef cattle; Fixed-time artificial insemination; GH; IGF-I; Leptin; Pregnancy